(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study endeavor to appreciation quality of Hilla river from through study some physicochemical parameters include PH, Temperature, Electrical conductivity, Total dissolved solid (TDS), salinity dissolved oxygen (DO), and (BOD5). Addition to estimate the level of bacterial contamination depending on which bacteria are used as indictor which encompass Total coliform, Total Escherichia coli, Total Enterococcus .Indicator bacteria isolate from water of Hilla river and the samples of water were collected along Hillah river once every season beginning in the October, 2016 even July 2017 the results showed divergence in consistency and number of microbial during four seasonal and stations The high number of microbial contamination recorded during Spring and lower number recoded during Winter. Total coliform were found in range of (3.02×103 to 7.74×103) cfu/100ml, Total E.coli ranged from (2.76×103 to 3.50×103) cfu/100ml and Enterococcus ranged from (o to 1.86×103) cfu/100ml, high number recorded during Spring and lower number recoded during summer. The study concerned the appreciation of the Hilla river as source of raw water with the aim of ensuring better water quality of the Hilla river in Iraq.